Perineal trauma during vaginal birth in Slovenia - Petra Petročnik; Ana Polona Mivšek; Teja Škodič Zakšek; Ivan Verdenik; Anita Jug Došler (Nurses and Midwives Association of Slovenia, 2018)
Introduction: The aim of this retrospective study was to examine the rates of perineal tears during childbirth in Slovenian  maternity hospitals in the period from 2013 to 2015. Methods: A causal non-experimental method of quantitative empirical approach was conducted. Data were pooled from the Slovenian National Perinatal Information System and analysed for the period of 2013 to 2015. Data analysis was performed with the use of frequency distribution of attributive variables and the basic descriptive statistics of numerical variables. Results: The incidence of perineal trauma during childbirth in all the 14 maternity hospitals varies from the "perineum without injury" to the "fourth degree perineal tear". Overall, 26.1 % of women sustained a first degree perineal tear, whereas 4.8 % of women had a second degree perineal tear. Severe perineal trauma included 0.8 % of third degree tears and 0.1 % of fourth degree tears. Discussion and conclusion: Perineal trauma varies between Slovenian maternity hospitals. Women who have sustained tears that cut into their bowels may face serious health problems and should be given relevant advice regarding the state of their pelvic floor after childbirth. It is of great importance to appropriately recognise the severity of the perineal trauma. Moreover, health professionals should be familiar with the perineal trauma classification and the factors that may cause the perineum to tear during childbirth.